2015
DOI: 10.1007/s11084-015-9449-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of Habitable Trojan Planets in Binary Star Systems

Abstract: Abstr actApproximately 60 percent of all stars in the solar neighbourhood (up to 80 percent in our Milky Way) are members of binary or multiple star systems. This fact led to the speculations that many more planets may exist in binary systems than are currently known. To estimate the habitability of exoplanetary systems, we have to define the so-called habitable zone (HZ). The HZ is defined as a region around a star where a planet would receive enough radiation to maintain liquid water on its surface and to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Astronomers found a large number of minor celestial bodies around these points of the planets of our Solar System and the Sun. The most well-known are the Greek and Trojan minor planets around the L4 and L5 points of the Sun-Jupiter system (Schwarz et al 2015, Schwarz & Dvorak 2012. Minor planets have also been found around the triangular Lagrange points of the Sun-Earth (John et al 2015), Sun-Mars (Christou 2017) and Sun-Neptune systems (Sheppard &Trujillo 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Astronomers found a large number of minor celestial bodies around these points of the planets of our Solar System and the Sun. The most well-known are the Greek and Trojan minor planets around the L4 and L5 points of the Sun-Jupiter system (Schwarz et al 2015, Schwarz & Dvorak 2012. Minor planets have also been found around the triangular Lagrange points of the Sun-Earth (John et al 2015), Sun-Mars (Christou 2017) and Sun-Neptune systems (Sheppard &Trujillo 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous works have shown that it is possible to exist stability in the co-orbital region of systems with much greater mass ratio values than those we have studied, such as trojan planets in binary star systems (e.g. Schwarz et al 2015).…”
Section: Mass Ratio Limitsmentioning
confidence: 67%
“…As these bodies were being discovered, many important works were made to study the co-orbital systems. There are studies on the dynamics in a restricted three-body problem (Danby 1964;Dermott & Murray 1981a;Lohinger & Dvorak 1993;Mittal et al 2020), on the stable regions around Lagrangian points (Deprit & Deprit-Bartholomé 1967;Marchal 1991;Érdi & Sándor 2005;Érdi et al 2007;Zhou et al 2009;Ćuk et al 2012), studies on the co-orbital regions of Solar System's planets (Mikkola & Innanen 1992;Nesvornỳ & Dones 2002;Scholl et al 2005;Tabachnik & Evans 2000), dynamics of some known co-orbital satellites (Dermott & Murray 1981b;Yoder et al 1983;Treffenstädt et al 2015), on stability and formation of the Solar System's trojans (Izidoro et al 2010;Donnison & Williams 1985;Chanut et al 2008;Mourão et al 2006;Pitjeva & Pitjev 2019;Zhou et al 2011Zhou et al , 2019Zhou et al , 2020Dvorak, R. et al 2012;Mikkola & Innanen 1990;Lykawka et al 2009Lykawka et al , 2011Marzari & Scholl 2013), and even hypothetical coorbital exoplanets (Schwarz et al 2009(Schwarz et al , 2012(Schwarz et al , 2015Beaugé et al 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…Supported by observations, many exoplanets are orbiting binary star systems, with nearly 70 exoplanets found in binary stellar systems (Schwarz et al 2015). This work studied the effects of stellar mass loss from one star in the inner binary system on its companion planetary orbit.…”
Section: Discussionmentioning
confidence: 99%